KAJIAN KARAKTERISTIK LAWAR BONGGOL PISANG (Musa sp) - Komalasari, Ni Nyoman Tribuana; Suter, I Ketut; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
This study aims to gather information of various banana corm effects to the characteristics of lawar . The RBD with single factor was used in this reseach. The type of banana corm used as a treatment that, consist of 6 level ie : raja banana corm, susu banana corm, kepok banana corm, emas banana corm, klutuk banana corm, and muli banana corm. Each treatment was repeated three times to obtain 18 experimental units. The variable observed were : proximate analysis (moisture, ash, protein, fat, carbohydrate), crude fiber, tannin, and sensory analysis ( color, aroma, texture, flavor and over all acceptance).  The data ware analysed by ANOVA test with a 5% significant level. If there was impact on the research, the analysis would be followed by Duncan's Multiple Range Test (DMRT). The results showed the use of various of banana corm give the significant effect to characteristics of lawar ie : proximate, crude fiber, tannin, and sensory properties. The best characteristics of lawar banana corm is resulted by klutuk banana corm (B5) which has moisture content 71.21%, ash 1.82%, protein 3.83%, fat 13.63%, carbohydrate 5.14%, crude fiber 10.33%, and tannin 0.28%. Sensory properties   color 5.7 (like), flavor 5.2 (a bit like), the texture 6.0 (like), taste 5.5 (rather like), and 6.2 overall acceptance (like).
Keywords: lawar, banana corm, crude fiber